Graft Survival after Penetrating Keratoplasty in Cases of Trabeculectomy versus Ahmed Valve Implant - Abdelhamid Elhofi; Hany Ahmed Helaly (Journal of Ophthalmology)
Purpose. To compare the corneal graft survival rates after penetrating keratoplasty (PKP) in cases of post-PKP glaucoma managed by either trabeculectomy with mitomycin C or Ahmed glaucoma valve (AGV). Methods. This study was a retrospective interventional comparative study that included 40 eyes of 40 patients. The included patients had undergone previous PKP for anterior segment reconstruction after microbial or fungal keratitis, chemical burns, trauma, or perforated corneal ulcer. Post-PKP glaucoma was managed surgically by either trabeculectomy with mitomycin C (group 1) or Ahmed glaucoma valve (group 2). Results. The first group n=20 had undergone trabeculectomy with MMC, and the second group n=20 had undergone AGV implantation. Regarding BCVA, there was no statistically significant difference between the 2 groups. Mean IOP was significantly lower in the AGV group at 6 months, 12 months, and 24 months p=0.001. Mean IOP at 24 months dropped significantly from preglaucoma surgery levels in both groups p=0.001. Rejection episodes occurred in 2 eyes (10%) of the trabeculectomy group versus 8 eyes (40%) in the AGV group p=0.028. In the trabeculectomy group, corneal graft failure occurred in 1 (5%), 3 (15%), and 6 (30%) eyes at 6 months, 12 months, and 24 months, respectively. In the AGV group, corneal graft failure occurred in 2 (10%), 5 (25%), and 10 (50%) eyes at 6 months, 12 months, and 24 months, respectively. The mean time to failure in the trabeculectomy group was 12.33 ± 5.60 months versus 11.90 ± 5.70 months in the AGV group p=0.027. Conclusion. Managing postpenetrating keratoplasty glaucoma could be bothersome especially in complex cases. Ahmed glaucoma valve implant controls the intraocular pressure more effectively than trabeculectomy with mitomycin C. However, Ahmed glaucoma valve can result in higher rates of corneal graft failure in a shorter duration of time. This trial is registered with PACTR201712002861391 on 21 Dec 2017.